Assessing Quality of Life, Well Being and Depression Among Iranian Ederly in Australia - Mahtab Alizadeh-Khoei; Soheyla Khosbin; Fereydon Khavarpour (University of Social Welfare & Rehabilitation Sciences, 2010)
Objectives: The aim of the study was to achieve the health status of the Iranian elderly migrants in Australia. Methods & Materials: This study was done as a cross sectional survey carried out in 2005-2007 on 302 Iranian immigrant aged 65 yrs and over who had lived in Sydney Metropolitan area for at least 6 months. Results: The majority of the Iranian elderly had a moderate level of anxiety and depression (44%) and more than half of them (58%) were experiencing average level of psychological wellbeing. From aspect of physical function (41%) Iranian elderly had moderate level of physical function as well as without limitation. With respect to daily living activity, the great part of the elderly participants (56%) were independent. The predictor variables of Socio-demographic and acculturation were strong significant variables in physical and mental health status of the Iranian elderly. Conclusion: Chronic medical conditions, Physical and social activity, and also accessing information and awareness of aged care services predicted both mental and physical health status of Iranian elderly respondents in this study (P≤0.001).